Developmental instability and plant potential fitness in a Mediterranean perennial plant, Retama sphaerocarpa (L.) Boiss - Fungairiño, S.G.; Fernández, C.; Serrano, J.M.; López, F.; Acosta, F.J. (Acta oecologica (Montrouge), 2005)
Developmental instability is manifested as developmental errors reflected in exaggerated intra-individual variation in repeated traits and patterns. Plants, as organisms with modular construction, are very suitable subjects for detecting developmental instability caused by environmental disturbance. The analysis of the asymmetry of plant structural traits allows for determination of deviations from the basic structural pattern, which is a measure of plant developmental instability. In this paper, we study the relationship between intra-individual variations on self-similar structural traits (as a measure of developmental instability) and plant potential fitness. Randomly-selected branches (composed of branch segments) were monitored on different plants of a natural population of the woody perennial plant Retama sphaerocarpa (L.) Boiss. Data on the morphology and the demographic processes that occurred during plant development (determined from marks left on the persistent structure of the plant) were recorded on the different branches. Different measures of developmental instability were analysed and related with plant potential fitness, which was estimated from the demographic data of the modules of each plant (bud development, branch survival, etc). Our results show a direct relationship between developmental instability measured on structural traits (except for branch segment diameter) and plant potential fitness, estimated by means of branch survival.